PENGALAMAN KOMUNIKASI ANGGOTA XBANK PEKANBARU - Nidya Havisyah Hikmah; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Xbank community is a non-profit community with a group of people who quit because of awareness of the danger of usury and religiously a grave sin consisting of former bank and non-bank employees who intend to seek halal and usury free sustenance. This community was formed to accommodate friends who intend to move, but are still in doubt due to various factors including themselves, economic conditions, environment and even family. This research aims to determine the motives and communication experiences of Xbank Pekanbaru members.This Research uses qualitative research methods with a phenomenological approach. The research subjects were 4 people who were selected using the snowball technique. Data collection was carried out out trough in-dept interviews, observation and documentation. In this study the authors used an interactive model of data analysis, to validate the data, the author used techniques, observational persistence and reference adequacy.The result showed that the motives of members of the pekanbaru xabnk doing hijrah consisted of because of motives which included self muhasabah, receiving guidance, and in order to motives including getting the pleasure od Allah. Motivating other and enforcing islamic sharia. Meanwhile, the communication experince of feeling happy can enforce islamic sharia, feel relieved and there is no burden on thoughts because of committing the sin of usury and receiving positive support from family and follow xbank member. For the unpleasant communication experince they experienced, namely, being ridiculed, scorned for being resign and being considered as self righteous.